Interrelation between birth weight, body mass index, insulin resistance, C-Reactive Protein-hs, adiponectin and leptin in children (Age 10 to 20 years) - Ravi R Thakre; S. S. Naik; S. A. Abhang (International Journal of Medical Research and Review, 2017)
Background: India is projected to have one of the largest populations of obese children over the next decade. Birth weight reflects maternal nutrition and fetal programming which may be a leading cause of obesity. Adipokines also play an important role in development of obesity, inflammation and insulin resistance. The aim of this study is to evaluate serum adiponectin, leptin in Indian school-going children in the age group of 10–20 years. This study also describes distribution of adipokines concentrations and examines the inter-relationship of adipokines with birth weight, body mass index (BMI), C - reactive protein high sensitive (CRP-hs), and insulin resistance (IR).Methods: A cross-sectional study involves a total of 200 school going children between the age group of 10-20 yrs. Fasting plasma glucose, insulin, adiponectin, leptin, CRP-hs, were measured for the school going children and birth weight was recorded.BMI was defined as weight (kg) divided by height (m) squared. Insulin resistance was assessed using the homeostasis model (HOMA-IR).Results: Children with higher BMI had higher birth weight and insulin. Obese children had lower adiponectin and higher leptin levels suggestive of an inverse association with adipokines. Children with higher BMI had lower glucose.Conclusion: Leptinan indicator of fat mass induces insulin resistance and inflammation. The derangement observed in all related parameters including insulin resistance, leptin, adiponectin and CRP-hs were due to high fat mass. However, the relationship of birth weight and adipokines needs further evaluation.